From Facilitator to Learning Coach: A Historical, Pedagogical, and Islamic Educational Perspective on English Language Teaching - Suhendra, Ade; Ilmi, Darul; Yanti, Fitri (STIT Ahlussunnah Bukittinggi, 2025)
The transformation of teachers’ roles from facilitators to learning coaches has become a pedagogical necessity in the era of globalization, particularly in English language teaching, which demands autonomous learning, metacognition, and 21st-century competencies. This article examines the shift through three lenses: the historical foundations of Islamic education, contemporary learning theories, and empirical findings from recent research (2017–2023). Using a systematic literature review, the study synthesizes evidence on the effectiveness of educational coaching and assesses its conceptual alignment with the Islamic conception of teachers mu’allim, murabbi, and muaddib. Findings indicate that learning coaching not only enhances instructional practice and students’ self-regulated learning (SRL) but also aligns with the core values and aims of Islamic education. The study proposes an integrative framework combining pedagogical, linguistic, character-based, and spiritual dimensions for English language learning in Islamic educational settings.